RADIOLOGICAL HEALTH IMPACT DUE TO ACTIVITY CONCENTRATIONS OF NATURAL RADIONUCLIDES IN THE SOILS FROM TWO MAJOR AREAS IN IJEBUNORTH LOCAL GOVERNMENT, OGUN STATE, NIGERIA - Alausa, S. K.; Odusote, O. O. (The Nucleus, 2013)
The soil samples from two major areas in Ijebu-North Local Government of Ogun State was analyzed for the concentrations of 40K, 226Ra and 232Th using gamma ray spectrometry method. The measured activity concentrations of 40K varied from 245.2 Bqkg-1 to 538.1 Bqkg-1 with a mean value of 367.9±74.1Bqkg-1 , 226Ra in the ranged from 10.4 Bqkg-1 to 30.2 Bqkg-1 with a mean value of 16.4±4.6Bqkg-1 and 232Th ranged from below detection limit (BDL) to 14.1Bqkg-1 with a mean value of 3.3±2.0Bqkg-1 . The mean external gamma absorbed dose rate in air at 1m above the ground level was 26.4±5.1 nGyh-1 which was just about one-half of 56.0 nGyh-1 recommended by UNSCEAR (2000). The mean annual outdoor effective dose rate was 32.3±6.3µSvy-1 . The collective dose equivalent was 9.18 manSv while the collective health detriment of the population was 0.15y-1 .